The Role of Growth Mindset and Academic Stress on Subjective Well-Being among College Students - Aulia, Zakia; Putri, Asri Mutiara; Lutfianawati, Dewi (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
Thecollege studentssubjective well-being indicates their contentment with several facets of campus life. This study aims to determine the role of growth mindset and academic stress on college students' subjective well-being. A total of 228 college students currently in their fourth to eighth semesters were involved in the study, selected using quota sampling. Data collection used the growth mindset instrument adapted from Chrisantiana and Sembiring, the perceived academic stress scale instrument developed by Bedewy and Gabriel, and the college student subjective well-being instrument developed by Renshaw, which has been adapted into Indonesian by Ariska et al.Results from multiple linear regressionanalysisindicatedthat growth mindsetandacademic stress together accounted for 46,1% ofthevarianceinsubjective well-being in college students.Academic stress was found to have a more significant impact on college students' subjective well-being compared to a growth mindset. The results of this study highlight the importance of reducing academic stress among college students to support their subjective well-being.Keywords:academic stress; college student subjective well-being;growth mindset